2015
DOI: 10.1353/jda.2015.0153
|View full text |Cite
|
Sign up to set email alerts
|

Development and income inequality: A new specification of the Kuznets hypothesis

Abstract: Substantial research has assessed the Kuznets hypothesis, which is a traditional relationship between inequality and development. The Kuznets hypothesis suggests that as development proceeds a country will experience first rising then falling income inequality. However, the existing literature analyzes the relationship between income inequality and per capita income, which is, at best, an incomplete measure of the multi-dimensional process of economic development. This paper explores the relationship between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
4
11
0
4
Order By: Relevance
“…Another part of the research was the estimation of models for an alternative approach to the EKC curve. Instead of the explanatory variable GDP, it was proposed to introduce the Human Development Index as the measure of economic affluence [78][79][80]. A mathematical formulation of the HDI is in the Human Development Report [15] (pp.…”
Section: Methodsmentioning
confidence: 99%
“…Another part of the research was the estimation of models for an alternative approach to the EKC curve. Instead of the explanatory variable GDP, it was proposed to introduce the Human Development Index as the measure of economic affluence [78][79][80]. A mathematical formulation of the HDI is in the Human Development Report [15] (pp.…”
Section: Methodsmentioning
confidence: 99%
“…Rarely do some studies use other variables for the income inequality than the Gini coefficient/ index. Such is the study of Huang et al (2012) who use the variables 'income shares of the top 10%, 5% and 1%' as proxies for income inequality, or the study of Theyson & Heller (2015) who use the Human Development Index. The Theil measure (how much individual country contributes to the global inequality) is also rarely used (Filauro, 2018).…”
Section: Methodology and Datamentioning
confidence: 99%
“…However, equally large number of studies shows evidence against the Kuznets hypothesis (although to the best of our knowledge the literature is extremely limited for the Balkan countries again). Theyson and Heller (2015) examine a large sample of 147 countries for the 1992 -2007 period and find that the use of different measures of development significantly affects the shape of the Kuznets curve. They use the Human Development Index as a proxy for income inequality and the results imply an S-curve instead of an inverted U-curve, meaning that at the beginning of a country's development, income inequality is falling, followed by a brief rise and then another fall in income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kuznets's hypothesis assumes that income inequality is higher in less developed countries. He found that for countries that longer belong to the group of developed countries, in the early stages of industrialization, income inequality increases first, and later when the "balancing forces become strong enough", income inequality stabilizes and finally is reduced (Theyson and Heller, 2015). This relationship is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 93%